PENYIMPANGAN DALAM PENERBITAN SERTIPIKAT HAK ATAS TANAH - Urip Santoso (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2013)
Salah satu kegiatan dalam hal pendaftaran tanah adalah diterbitkannya sertipikat hak atas tanah sebagai tanda bukti hak oleh Kantor Pertanahan. Dengan diterbitkan sertipikat ini, nantinya akan dengan mudah dapat dibuktikan siapa pemegang haknya. Dengan diterbitkan sertipikat, akan terwujud jaminan kepastian hukum dan perlindungan hukum bagi pemegang haknya. Pada kenyataan dalam praktiknya, terjadi tindakan penyimpangan dalam penerbitan sertipikat, yang mana hal ini terjadi dalam beberapa bentuk, yaitu diterbitkannya sertipikat palsu, sertipikat asli namun ternyata palsu, sertipikat ganda, sertipikat tumpang tindih, dan juga sertipikat fiktif.One thing that is required in land registration activity is the issuance of the certificate of land rights by the land office, which is used commonly as an evidence. By the issuance of this certificate, it will ease the process of proofing the ownership of the related land. The issuance of this certificate will definetely realize the legal certainty and legal protection to the owner. In fact, there was an act of irregularities in the issuance of certificates, which occured in several forms, such as the issuance of fake certificates, original certificates but apparently false, multiple certificates, certificates of overlap, as well as fictitious certificates.